2016
DOI: 10.1016/j.bbrc.2016.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived high-mobility group box 1 promotes recruitment and suppresses apoptosis of monocytes

Abstract: Platelets are circulating cellular sensors that express and release the damage-associated molecular pattern molecule (DAMP) high-mobility group box 1 (HMGB1) at sites of disrupted vascular and tissue integrity. We have recently identified platelet-derived HMGB1 as a critical mediator of thrombosis. The role of platelet-derived HMGB1 in mediating interactions with monocytes remains unknown. In transgenic mice with platelet-specific ablation of HMGB1 and neutralization studies, we show that HMGB1 derived from pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…Even under SCD steady state conditions, circulating platelets are significantly activated in patients, and are further activated in vaso-occlusive crisis and acute clinical events, such as acute chest syndrome (Westwick et al, 1983;Wun et al, 1997;Villagra et al, 2007;Garrido et al, 2017). Beyond their role in haemostasis, platelets provide a link between thrombosis and inflammation (Semple et al, 2011;Rondina et al, 2013;Morrell et al, 2014;Vogel et al, 2015aVogel et al, , 2016Murthy et al, 2017). More than two decades ago, Brittain et al (1993) proposed that activation of platelets has a contributory role in sickle vaso-occlusions.…”
Section: Platelets In Sickle Cell Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Even under SCD steady state conditions, circulating platelets are significantly activated in patients, and are further activated in vaso-occlusive crisis and acute clinical events, such as acute chest syndrome (Westwick et al, 1983;Wun et al, 1997;Villagra et al, 2007;Garrido et al, 2017). Beyond their role in haemostasis, platelets provide a link between thrombosis and inflammation (Semple et al, 2011;Rondina et al, 2013;Morrell et al, 2014;Vogel et al, 2015aVogel et al, , 2016Murthy et al, 2017). More than two decades ago, Brittain et al (1993) proposed that activation of platelets has a contributory role in sickle vaso-occlusions.…”
Section: Platelets In Sickle Cell Diseasementioning
confidence: 99%
“…HMGB1 and TLR4 are key players in promoting inflammation in SCD (Xu et al, 2014). Targeted ablation of HMGB1 and TLR4 in circulating platelets in transgenic mice promoted anti-thrombotic and antiinflammatory effects (Vogel et al, 2015a(Vogel et al, , 2016. The HMGB1 inhibitor Glycyrrhizin (Mollica et al, 2007), a triterpene glycoside extracted from liquorice root, exerted potent inhibitory effects on platelet HMGB1 signalling (Vogel et al, 2014(Vogel et al, , 2015a.…”
Section: Targeting Hmgb1 and Nlrp3 Signalling In Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet-derived HMGB1 has been shown to promote the recruitment of monocytes, and lead to inflammation and thrombosis [13]. Disulfide (or isomerized) HMGB1, characterized by 2 cysteine residues that are oxidized to form an S-S bond between C23 and C45, was found to induce NF-κB translocation and the secretion of inflammatory factors via TLR-4 in activated immune cells, while mutations of C23 or C45 abrogated the cytokine activity of HMGB1 [14].…”
Section: The Role Of Hmgb1 As a Redox Regulatormentioning
confidence: 99%
“…Studies addressing the role of HMGB1 in myocardial infarction (MI) have generated conflicting results thus far, as detrimental [3-5] as well as salutary effects of HMGB1 [6-8] have been reported. Platelets store and, upon activation, export HMGB1 to the cell surface and release HMGB1 in significant amounts [9-11]. In a trauma/hemorrhagic shock model in mice with platelet-specific ablation of HMGB1, we have recently shown that platelet-derived HMGB1 is a critical mediator of thrombosis [9].…”
Section: Introductionmentioning
confidence: 99%